3. Products and Coproducts
Definition 3.1. Suppose f, g:
Y --> X is a pair of morphisms in a category. An equalizer of
f, g is a morphism k: K --> Y of objects such
that fk = gk, which has the universal property that, if m:
M --> Y is another morphism of objects with fm = gm, then there
is a unique morphism n: M --> K such that m = kn.
The equalizer of a pair of morphisms, if exists, is uniquely determined
up to an isomorphism.
Example 3.1.1. Suppose u,
v: Y --> X is a pair of functions of sets. Let K = ker(u,
v) = {a Y | u(a)
= v(a)}. Then the inclusion function
k: K --> Y
is an equalizer of u, v in the category of sets.
Proposition 3.2. Suppose f,
g: Y --> X is a pair of morphisms. Let K = ker(f,
g) = {a Y | f(a)
= g(a)} be the equalizer of f, g in the category of sets.
Then K is a closed subset of Y. The subobject K with
the inclusion morphism is a equalizer of f, g in A.
Proof. Let d: Z[K] --> Y be the morphism
induced by inclusion of K --> Y. Then fd = gd. So d(Z[K])
= K as K is the equalizer of f, g in the category
of sets. Thus K = G(K) implies that K is a closed
subset of Y. Any morphism t: T --> Y such that ft
= gt factors through K in a function m, which must be
a morphism by (2.8.c). Thus K is the equalizer of f, g
in A.
Definition 3.3. Suppose {Xi}
is a set of objects in a category. A product
of {Xi} is an object X, together with a collection
of morphisms pi: X --> Xi, with the
universal property that, if Y is another object together with a
collection of morphisms ti: Y --> Xi,
there is a unique morphism s: Y --> X such that ti
= p1s for each i.
Example 3.3.1. If {Xi}
is a set of sets, the product set i
Xi together with the projections i
Xi --> Xi is the product of {Xi}
in the category of sets.
Proposition 3.4. Suppose {Xi}
is a set of objects. Then there is unique algebra structure on the product
set i Xi
such that the projections i
Xi --> Xi are morphisms, which is the product
of objects {Xi} in A.
Proof. For simplicity we give the proof for the product of two
objects X and Y. The general case is similar. The projections
p1,
p2 of X
Y determines two projections q1: Z[X
Y] --> X and q2: Z[X
Y] --> Y extending p1, p2 , which
then induces a function t: Z[X
Y] --> X Y extending
the identity function of X
Y such that q1 = p1t and q2
= p2t. Let s: X
Y --> Z be the surjective generic extension of t. Then there
are morphisms u: Z --> X and v: Z --> Y such
that us = p1 and vs = p2. Also u
and v induces a function s': Z --> X
Y such that p1s' = u and p2s' = v.
Thus we have p1s's = p1 and p2s's
= p2, which implies that s is injective, therefore
bijective. By (1.2) X Y
carries an algebraic structure such that s is an isomorphism. Then
p1
= us and p2 = vs are morphisms.
Next consider two morphisms u: W --> X and v:
W --> Y. They induces a function r: W --> X
Y such that u = p1r and v = p2r.
Let t': Z[W] --> W be the canonical morphism
and r': Z[W] --> Z[X
Y] be the morphism induced by r. Then p1rt' =
q1t' = p1tr' and p2rt' = q2t'
=p2tr' implies that rt' = tr'. Since t' is
surjective and tr' is a morphism of objects, by (2.3.b) r
is a morphism. This shows that the object X
Y is the product of X with Y. The uniqueness of the algebraic
structure on X Y also
follows from this and (1.2).
Definition 3.5. Let f: Y -->
S and g: X --> S be two morphisms of objects. A fibred
product of X and Y over S is an object
X
S Y, together with two morphisms p1:
X S Y --> X
and p2: X S
Y --> Y such that fp1 = gp2, which has
the universal property that, if u: Z --> X and
v:
Z --> Y are two morphisms of objects such that fu = gv, there
is a unique morphism t: Z --> X S
Y such that u = p1t and v = p2t.
Example 3.5.1. Let f: Y -->
S and g: X --> X be two functions of sets. Let X S
Y = {(a, b)| a in X and b in
Y such
that f(a) = g(b)}. Then X S
Y together with the projection p1: X
S Y --> X sending (a, b) to a, and the projection
p2: X S
Y --> Y sending (a, b) to b, is the fibre product of
X and
Y over S in the category of sets.
Proposition 3.6. Suppose f:
Y --> X is a morphism of objects. Then Y X
Y is a closed subset of Y
Y. The subobject Y X
Y, together witht the projections p1, p2:
Y X Y is the
fibre product of Y and X over S.
Proof. Consider the morphism h: Z[Y X
Y] --> Y Y determined
by the inclusion Y X
Y --> Y Y. Let p1,
p2 be the projections of Y X
Y. Then p1h = p2h, which implies that
h(Z[Y X
Y]) Y X
Y. Thus Y X
Y is a closed subset of Y
Y. It is straightforward to verify that Y S
X is the fibre product of Y and X over S.
Definition 3.7. Suppose fi,
gi: Y --> X is a set of pairs of morphisms. A common
coequalizer of {fi, gi} is a morphism
k:
X --> K of objects such that kfi = kgi
for all i, with the universal property that, if m: X -->
M is another morphism of object with mfi = mgi
for all i, then there is a unique morphism n: K --> M
such that m = nk.
Proposition 3.8. Any set fi,
gi: Y --> X of pairs of morphisms has a common coequalizer.
Proof. Let i
Xi be the products of X = Xi with itself
indexed by i. Let f: Y -->
Xi be the morphism determined by fi:
Y --> X = Xi. Let g: Y -->
Xi be the morphism determined by gi:
Y --> X = Xi. Then the equalizer of f, g is
the common equalizer of fi, gi.
Definition 3.9. Suppose {Xi}
is a set of objects. A coproduct of
{Xi} is an object X, together with a collection
of morphisms qi: X1 --> X, with the
universal property that, if Y is another object together with a
collection of morphisms ti: Xi --> Y,
there is a unique morphism s: X --> Y such that ti
= sp1 for each i.
Proposition 3.10. Suppose {Xi}
is a set of objects. Let ri: Xi --> Z[ i
Xi] be the inclusions. Then there is a unique surjective
morphism t: Z[ i
X] --> B such that each tri is a morphism
and (B, {tri}) is the coproduct of {Xi}.
Proof. For simplicity we give the proof for the coproduct of
two objects X and Y. The general case is similar. Let r:
X --> Z[X Y] and
s:
Y --> Z[X Y] be
the inclusions. Consider the two morphisms u: Z[X]
--> Z[X Y] and
v:
Z[Y] --> Z[X
Y] determined by the inclusion X --> X
Y and Y --> X Y.
Let a: Z[X] --> X and b: Z[Y]
--> Y be the canonical morphisms. Let t: Z[X
Y] --> B be the common coequalizer of (u, ra) and (v,
sb). First tra = tu and a is a surjective morphism, and
tu
is a morphism implies that tr is a morphism. Similarly
ts
is a morphism. Next assume f: X --> B' and g: Y
--> B' are any two morphisms. Let t': Z[X
Y] --> B' be the morphism induced by the function (f, g):
X Y --> T. Then hu
= fa. But f = hr. So hu =hra. Similarly hv = hsb.
Since t is the common coequalizer of u, ra and v, sb,
there is a unique morphism k: B --> T such that h = kt.
Then f = hr = ktr and g = hs = kts. The uniqueness of k
is obvious. This shows that (B, tr, ts) is a sum of X,
Y.
[Next Section][References][Notations][Home]
|